PERSEPSI MASYARAKAT KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR, MENGENAI MERGER TIGA BANK SYARIAH MENJADI BANK SYARIAH INDONESIA - Astuti, Riani; Thantawi, Tubagus Rifqy; Mursyidah, Azizah (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
A Bank is a financial intermediary or can be called a financial intermediary, meaning that a bank institution is an institution whose activities are related tp money matters. To avoid operating a bank with an Islamic interest system, introducing the principles of Islamic muamalah, Islamic banks were born as an alternative solution to the problem of conflict between bank interest and usury. The problem in this thesis is the perception of Islamic bank products is the level of knowledge and understanding of customers about Islamic bank products and services. Bank products are oflen chosen by customers based on aspects of information regarding the benefis to be obtained from these bank products, but the lack of understanding, information and inadequate promoyion of bank products causes deviations in bank business activities that can harm customers and allow potential customers not to interested in choosing products owned by the bank. In the discussion of this thesis, the researcher uses a qualitative research type. The sample in this study were 25 respondents. Data were taken by interview. Then the researcher processes the data by doaing data reduction, presenting the data, and drawing conclusions or verification. Based on the research that researchers have done, it is found that public perception is quite good and many people have also used Islamic bank. Of the 25 people interviewed, 16 people of 64% have become customers of the merged sharia bank, while the remaining 9 people or 36% have not become customers of the merged sharia bank. However, people still find it difficult to get ATM facilities, because there are still uneven placement of ATM machines in Cibungbulang District, so that to use ATM facilities, people have to look outside Cibungbulang District, while M-Banking facilities are still constrained by signals and frequent disturbances